Cell-free Mycobacterium tuberculosis DNA test in pleural effusion for tuberculous pleurisy: a diagnostic accuracy study. (August 2020) - Yang, X.; Che, N.; Duan, H.; Liu, Z.; Li, K.; Li, H.; Guo, C.; Liang, Q.; Yang, Y.; Wang, Y.; Song, J.; Du, W.; et al.
Abstract: Objectives: Tuberculous pleurisy (TP) diagnosis remains difficult, with the sensitivity of Xpert MTB/RIF (Xpert) and mycobacterial culture (culture) only about 30–50%. We aimed to assess the diagnostic performance of a cell-free Mycobacterium tuberculosis DNA test (cf-TB) in pleural effusion for TP. Methods: Adults (≥18 years) with suspected TP presenting with pleural effusion were consecutively recruited, and pleural effusion specimens were prospectively collected in Beijing Chest Hospital, Beijing, China. After centrifuging pleural effusion, sediments were used for culture, Xpert and T-SPOT.TB assay, whereas supernatants were used for cf-TB and adenosine deaminase assay. The diagnostic performance was assessed against a composite reference standard. Results: From June 2015 to December 2018, we prospectively evaluated 286 adults with suspected TP. One hundred twenty-two participants were classified as definite TP based on the prespecified composite reference standard. The cf-TB produced a sensitivity of 79.5% (97/122, 95% confidence interval (CI) 72.4– 86.7) for definite TP, which was superior to Xpert (38.5% (29.9–47.2); 47/122; p < 0.001) and culture (27.1% (19.2–34.9); 33/122; p < 0.001). With pleural effusion Xpert and/or culture as the reference standard, cf-TB showed 96.6% (57/59, 95% CI 92.0–100.0) sensitivity, which was also significantly higher than Xpert (79.7%, 95% CI 69.4–89.9; 47/59; p 0.004) and culture (55.9%, 95% CI: 43.3–68.6; 33/59; p < 0.001). Conclusions: The cf-TB clearly showed improved sensitivity compared with Xpert and culture. We recommend cf-TB as the first-line test for TP diagnosis.